Experiences of health care professionals on the implementation of Central Chronic Medicine Dispensing and programme at Bafokeng Health Centre, North West Province - Masakona, Mudindivhathu (My University, 2024)
Introduction and background: Overcrowding in the health facilities has impacted the quality of health services that is rendered to patients. Different strategies aiming to reduce the number of patients at health facilities were adopted including the CCMDD programme. Aim: To determine the experiences of Health care professionals on the implementation of the Central Chronic Medicine Dispensing and Distribution programme. Methodology: A qualitative exploratory study design has been used to explore the experiences of HCPs on the implementation of Central Chronic Medicine Dispensing and Distribution (CCMDD). Unstructured one-on-one interviews were used to gather the data from health care professionals implementing the CCMDD programme at Bafokeng health centre, North West. Nine registered nurses and one pharmacist were sampled through a non probability sampling method. Open-ended questions were asked, and the interview was recorded for further analysis. Thematic analysis method was used to analyse the collected data. The data was coded by the researcher and co-coded by a professional coder. Results: The study revealed that CCMDD has decongested health care facility, reduced staff workload and patients waiting time. Challenges experienced during the implementation of CCMDD were revealed and recommendations were made to the department of health, nursing education and future researches. Conclusion The study findings indicate that the CCMDD programme is an effective strategy that has benefited the patients, health care professionals and the department of health. The conclusion is drawn from participants’ unanimous agreements that the programme has brought significant change on them and the patients. The researcher further concludes that the programme plays a role in motivating patients to adhere to their treatment
Thesis (MPH.) -- University of Limpopo, 2024
Keywords: Health care professionals; Central chronic medicine dispensing and distribution; Bafokeng Health Centre; North West Province; Medical personnel; Health facilities -- Design and construction; Pharmaceutical industry; Medicine